2022
DOI: 10.3390/lubricants10120358
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Modelling of Viscoelastic Contact Problems

Abstract: Approaches to solving viscoelastic problems have received extensive attention in recent decades as viscoelastic materials have been widely applied in various fields. An overview of relevant modelling approaches is provided in the paper. The review starts with a brief introduction of some basic terminologies and theories that are commonly used to describe the contact behaviour of viscoelastic materials. By building up the complexity of contact problems, including dry contact, lubricated contact, thermoviscoelas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 185 publications
0
9
0
Order By: Relevance
“…Nineteen viscoelastic models were summarized by Neville et al [ 35 ] and it was concluded that, when the number of elements is too large, some ill-posed problems are introduced. Therefore, simplifying the number of elements and parameters of the viscoelastic model not only facilitates the calculation process, but also helps to clarify the physical meaning of the model parameters [ 36 ].…”
Section: Comparisons Between Experimental Results and Predictionsmentioning
confidence: 99%
“…Nineteen viscoelastic models were summarized by Neville et al [ 35 ] and it was concluded that, when the number of elements is too large, some ill-posed problems are introduced. Therefore, simplifying the number of elements and parameters of the viscoelastic model not only facilitates the calculation process, but also helps to clarify the physical meaning of the model parameters [ 36 ].…”
Section: Comparisons Between Experimental Results and Predictionsmentioning
confidence: 99%
“…In the last couple of years, the VESevo technology has been used in a wide range of applications, each usually proposed by new kinds of users, proposing procedures linked to their areas of interest: Providing measurements to objectivize the differences among the various compounds used for tire treads (with important impacts on determining the optimal thermal window in which each compound has to be used), getting data for FEA (finite element analysis) [ 16 ], CFD (computational fluid dynamics) [ 17 ], friction [ 18 ], and wear [ 19 ] models, both in motorsport and passenger contexts; assessing the optimal vulcanization and manufacturing setup conditions, with a direct evaluation of their effects, from the tire just produced to its progressive degradation in the aging process acting in the lifecycle, or helping to define the optimal “curing cycles”; the motorsport teams are used to apply to the tires to enhance their adhesive and hysteretic frictional attitudes; monitoring the evolution of the viscoelastic characteristics due to wear (conceived as both progressive tread thickness reduction [ 20 ] under tangential interaction stresses and progressive mechanical degradation due to hysteretic cycles and chemical decay [ 21 ]) during the whole life of the tested tire, allowing to correlate the energy provided to it (for frictional forces, for rolling resistance cycles, for UV radiation effect) with the direct effects on the material, observable from its first instant of life, to the ultimate phase of use; improving the effectiveness of the on-site quality control methodologies [ 22 ], acting as a sort of “fast and portable DMA” directly on the tire production line, checking the viscoelastic uniformity along the circumferential and transversal direction for car, truck, aircraft, motorcycle, and bike tires, and for slick or ribbed tread patterns. …”
Section: Introductionmentioning
confidence: 99%
“…Providing measurements to objectivize the differences among the various compounds used for tire treads (with important impacts on determining the optimal thermal window in which each compound has to be used), getting data for FEA (finite element analysis) [ 16 ], CFD (computational fluid dynamics) [ 17 ], friction [ 18 ], and wear [ 19 ] models, both in motorsport and passenger contexts;…”
Section: Introductionmentioning
confidence: 99%
“…The case of a Kelvin-Voigt solid (with accounting for the unloading stage) was considered by Khusid [51] (see also [29]), who obtained some numerical results for the impact duration and the coefficient of restitution. A systematic review of modeling linear and non-linear viscoelastic contact problems was recently given by Wang et al [52].…”
Section: Introductionmentioning
confidence: 99%